An Overlooked Disease: Minimal Autonomous Cortisol Secretion (MACS). A Narrative Review - Farah, Stephanie; Nasr, Leah; Eid Fares, Jocelyne (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: A far more common disease than Cushing's syndrome is subclinical hypercortisolism or mild autonomous cortisol secretion (MACS), with an overall prevalence of 0.2-2%. Objective: This review aims to shed light on the prevalence, screening and diagnostic criteria, comorbidities, and management of Mild Autonomous Cortisol Secretion (MACS). Methods: Studies eligible targeted MACS regarding prevalence, screening, comorbidities, management, and clinical outcome. This is a narrative-review. IRB approval was not needed. Results: The 1 mg Dexamethasone suppression test (DST) remains the first screening test. MACS is associated with adverse cardiometabolic and renal outcomes, osteoporosis and osteopenia, immunodeficiency, depression, coagulopathy, and sarcopenia. Surgery is the gold standard treatment. Medical therapy is recommended when surgery is contraindicated or not feasible. Clinically silent hypercortisolism is a frequent entity that necessitates early detection and treatment. The production of cortisol should be looked at as a spectrum where subtle, undetectable levels can still be produced. They know its association with adverse health outcomes. Conclusion: MACS is no longer considered an asymptomatic disorder; repeated hormonal and functional tests are crucial to prevent multiorgan damage.
Keywords: screening